Validity and reliability of sprint force-velocity profiling in elite football: Comparison of MySprint, GPS, and radar devices - Stockdale, R. A.; Dos`Santos, T.; McDaid, K.; Nagy, P.; Gaffney, C. J.; Barry, T. J. (PLOS ONE, 2025)
The aims were to examine the validity and within-session inter-trial, intra- and interrater reliability of sprint force-velocity profiling (FVP) techniques in elite football. Twelve elite youth football players from an English Premier League academy participated in this study. A 30-m maximal effort linear sprint testing protocol was conducted, simultaneously measured using the MySprint app, GPS units, and radar device to derive theoretical maximal horizontal force (F0), theoretical maximal running velocity (V0), and the overall orientation of the profile (FVslope). There were significant differences in F0, V0, and FVslope (p < 0.05) between the MySprint app and radar device, with large effect sizes (e2 = 0.683, 0.513, and 0.482), but not in F0 or V0 (p > 0.05), between the GPS and radar devices. There were no significant differences in F0 or V0 (p > 0.05) between each players` sprint repeats for all equipment types, with these effect sizes (rrb): MySprint (0.047, 0.523), GPS (0.236, -0.163), radar (0.785, -0.777). RMSE and CV values for F0 and V0 were 0.72-1.20 N/Kg and 3.76-9.59%, 0.21-0.40 m/s and 1.48-2.64%, respectively, with improved reliability and agreement in V0 vs. F0. There was no significant difference in F0 or V0 (p > 0.05), with medium-to-large effect sizes (rrb = -0.242 and -0.636) when the MySprint analysis was repeated by the same rater. RMSE and CV values for F0 and V0 were 0.19 N/Kg and 2.9%, 0.07 m/s and 0.54%. There was no significant difference in F0 or V0 (p > 0.05) between the two raters` MySprint analysis, and ICC demonstrated excellent agreement (F0 = 0.986, CI = 0.950-0.996, and V0 = 0.988, CI = 0.957-0.997). This study reports high intra- and inter-rater reliability when using the MySprint app to derive FVP`s from 30-m maximal sprint testing whilst indicating GPS as the most valid and reliable force-velocity profiling technique against the reference radar device.